2013
DOI: 10.1111/psyp.12077
|View full text |Cite
|
Sign up to set email alerts
|

Motivation enhances visual working memory capacity through the modulation of central cognitive processes

Abstract: Motivation is well known to enhance working memory (WM) capacity, but the mechanism underlying this effect remains unclear. The WM process can be divided into encoding, maintenance, and retrieval, and in a change detection visual WM paradigm, the encoding and retrieval processes can be subdivided into perceptual and central processing. To clarify which of these segments are most influenced by motivation, we measured ERPs in a change detection task with differential monetary rewards. The results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…The general prospect of receiving reward can boost visual working memory capacity, most likely via an increase in motivation. When information about the amount of reward that can be earned is provided at the beginning of each trial, memory performance has been found to be better when a high reward can be earned than when a low or no reward can be earned (Kawasaki & Yamaguchi, 2013;Krawczyk, Gazzaley, & D'Esposito, 2007;Sanada, Ikeda, Kimura, & Hasegawa, 2013). Motivational value can not only globally enhance memory performance, but also modulate working memory for specific stimuli or features, with better performance for items associated with a high reward (Gong & Li, 2014;Klink, Jeurissen, Theeuwes, Denys, & Roelfsema, 2017;Thomas, FitzGibbon, & Raymond, 2016;Wallis, Stokes, Arnold, & Nobre, 2015), and worse performance for value-neutral items that are presented along with highly rewarded items (Infanti, Hickey, & Turatto, 2015) or items that were associated with a loss (Thomas et al, 2016).…”
Section: Motivational Valuementioning
confidence: 99%
“…The general prospect of receiving reward can boost visual working memory capacity, most likely via an increase in motivation. When information about the amount of reward that can be earned is provided at the beginning of each trial, memory performance has been found to be better when a high reward can be earned than when a low or no reward can be earned (Kawasaki & Yamaguchi, 2013;Krawczyk, Gazzaley, & D'Esposito, 2007;Sanada, Ikeda, Kimura, & Hasegawa, 2013). Motivational value can not only globally enhance memory performance, but also modulate working memory for specific stimuli or features, with better performance for items associated with a high reward (Gong & Li, 2014;Klink, Jeurissen, Theeuwes, Denys, & Roelfsema, 2017;Thomas, FitzGibbon, & Raymond, 2016;Wallis, Stokes, Arnold, & Nobre, 2015), and worse performance for value-neutral items that are presented along with highly rewarded items (Infanti, Hickey, & Turatto, 2015) or items that were associated with a loss (Thomas et al, 2016).…”
Section: Motivational Valuementioning
confidence: 99%
“…Not surprisingly, high motivation enhances performance (Brose, Schmiedek, Lovden, & Lindenberger, 2012; Krawczyk & D’Esposito, 2013; Roets, Van Hiel, & Kruglanski, 2013; Sanada, Ikeda, Kimura, & Hasegawa, 2013; Unsworth & McMillan, 2013). Neuroimaging data demonstrate differential processing when participants are extrinsically motivated through financial incentives.…”
Section: 1 Introductionmentioning
confidence: 98%
“…Neuroimaging data demonstrate differential processing when participants are extrinsically motivated through financial incentives. For instance, high reward WM trials significantly improved behavioral performance and modulated late-trial components of the event-related potential (ERP) (Sanada et al, 2013). Furthermore, extrinsic motivation differentially activates regions in the PFC and visual association regions (Krawczyk & D’Esposito, 2013).…”
Section: 1 Introductionmentioning
confidence: 99%
“…The results of this study contrasted with the study of Gholizadeh et al ( 24 ). It seems that the visual memory is related with various variables, such as intelligence ( 29 – 31 ), critical thinking ( 32 ) and motivation ( 33 ) that are not assessed in this study. Since the encoding zone, verbal memory and working verbal memory are on the left side of the brain and visual-spatial memory is on the right side of the brain, and given that the reference electrode was placed on the left side of the head in this study, and as a result, the left side of the brain was further under beta waves, perhaps it was more effective on verbal memory and was less effective on visual memory.…”
Section: Discussionmentioning
confidence: 82%